Reduced heart rate response to exercise in patients with type 2 diabetes - Jingfeng Lou; Hongmei Lang; Yuhan Xia; Hui Jiang; Hui Jiang; Kun Li; Kun Li; Xingping Zhang (Frontiers in Cardiovascular Medicine)
BackgroundRecent studies have found that heart rate response is impaired in patients with type 2 diabetes. However, it remains unclear how chronotropic competence changes in these patients and which chronotropic index is more closely related to type 2 diabetes. This study aims to investigate the changes in chronotropic competence in type 2 diabetes and compares the association of two different chronotropic indices with type 2 diabetes.Patients and methodsPatients who underwent cardiopulmonary exercise testing at the Chengdu Second People's Hospital from October 2022 to October 2023, we included. Logistic regression was used to analyze the relationship between chronotropic indices and type 2 diabetes, comparing which of the two chronotropic indices is more closely related to type 2 diabetes.ResultsA total of 166 patients were included in our study, of which 42.8% had type 2 diabetes and 57.2% did not have type 2 diabetes. After adjusting for confounders, the OR for chronotropic index 1 with type 2 diabetes was 0.001 (95% CI: 0.0001–0.521, P = 0.03), and the OR for chronotropic index 2 with type 2 diabetes was 0.665 (95% CI: 0.479–0.923, P = 0.015), both showing a negative correlation with type 2 diabetes. When chronotropic index 2 was included in the model as quartiles, it still showed a negative correlation with type 2 diabetes (OR: 0.388; 95% CI: 0.173–0.869; P = 0.021), while chronotropic index 1 showed no significant correlation.ConclusionHeart rate response is reduced in patients with type 2 diabetes, and a low chronotropic index 2 is independently associated with type 2 diabetes.